Glatt! From suburb to city? - (:unkn) unknown (Park Books, 2013)
With its book Glatt! Manifest für eine Stadt im Werden, the Architects Group Krokodil proposed an increase in the density of the agglomeration to turn it into a city. Instead of Glatttal: Glatt-the City! The International Summer Academy Zurich presented this urban vision as a subject for discussion. In 10 studios roughly 100 students from all around the world questioned the Krokodil Group's hypotheses and urban design. Glatt! From Suburb to City tells the story of this Summer Academy and in the form of essays and statements, an encyclopedia, and the results of the individual studios, writes the next chapter in the history of the virtual City of Glatt.
Keywords: Stadtplanung; Neue Stadt; Stadtumland; Zersiedelung; Suburbanisierung; Verdichtungsraum; Urbanismus; Zwischenstadt; Visualisierung; Agglomeration